MEMBANGUN KESADARAN KEBERSIHAN LINGKUNGAN DAN KEPEDULIAN SESAMA DI KAMPUNG KAPASARI 3 SURABAYA - Michael Kevin; Laurensius Sean; Maria Nevenda; Prahesti Jihan; Agrienta Bellanov (ABIDUMASY, 2022)
Covid-19 is a dangerous disease caused by a virus and has a rapid rate of development. The Covid-19 virus is known to have entered Indonesia since the beginning of 2020, and continued to take many victims until the end of 2021. The Minister of Health and the government are trying to reduce the number of Covid-19 victims by inviting all people to be diligent in wearing masks when in public places, diligently washing hands and not forgetting to always carry hand sanitizers. This virus seems to be a reminder of the importance of maintaining personal hygiene and the surrounding environment. Over time, this dangerous virus is decreasing, but of course it doesn't necessarily make people careless and forget the habit of maintaining personal and environmental hygiene. Therefore, the community service team together with Darma Cendika Catholic University students mingled with the community in Kampung Kapasari Pedukuhan 3 Surabaya to clean the environment, provide trash can facilities, distribute hand sanitizers, basic necessities, and socialize related to public awareness to protect the environment.